Theoretical Investigation of Hydride Insertion into N‐Heterocyclic Carbenes Containing N, P, C, O and S Heteroatoms. Issue 23 (24th October 2018) - Al Furaiji, Khalidah H. M.; Iversen, Kalon J.; Dutton, Jason L.; Wilson, David J. D.
Abstract: The endocyclic ring expansion of N‐heterocyclic carbene (NHC) rings containing one N atom and one P, N, C, O or S heteroatom has been investigated in a computational study. Ring expansion was determined to follow a common pathway, leading to a final expanded six‐membered ring that was predicted to be thermodynamically stable for all heterocycles. However, reactivity is driven by kinetics with ring‐expansion reactivity not expected for the P/NHC and C/NHC (cAAC) containing heterocycles due to large barriers for ring‐expansion. In contrast, ring expansion is predicted to be feasible for N‐heterocyclic carbenes containing an O (O/NHC) or S (S/NHC) heteroatom, with insertion into the O−C and S−C bond favoured over insertion into the N−C bond, respectively. Abstract : This study rings true : A theoretical investigation of N‐heterocyclic carbenes with mixed heteroatoms indicates that previously unobserved hydride ring expansion of NHCs containing an O or S atom may occur. Insertion into the O−C or S−C bond is favoured over N−C insertion. Ring expansion is not expected with NHCs containing a P heteroatom.